Performance of automotive air conditioning system using al2o3-sio2 nanolubricants - Nurul Nadia, Mohd Zawawi (2021)
Enhancement in the coefficient of performance (COP) of the automotive air conditioning (AAC) system is necessary to reduce fuel consumption. A novel approach for improvement in refrigeration system performance is by dispersing nanoparticles in the conventional lubricant of AAC compressor. However, single-component lubricant applications contribute limitations on stability, compressor work, wear rates and AAC performance. The recent trend in nanoparticle dispersion technology is by utilizing two or more metal or metal oxide nanoparticles in existing lubricant and is known as composite nanolubricants. The composite nanolubricants is expected to improve the properties of single-component nanolubricants in achieving enhancement in thermal properties, rheological properties, stability, and AAC system performance. The aims of the present study are to evaluate the properties of metal oxide composite nanolubricants and to investigate the optimum condition of the AAC system performance using the best combination of composite nanolubricants. Metal oxide nanoparticles were dispersed in the Polyalkylene Glycol (PAG) 46 lubricant with different combinations of two types of nanoparticles using the two-step method of preparation. The composite nanolubricants was prepared up to 0.1% volume concentration with a variation of nanoparticle composition ratios. Thermal physical properties of different metal oxide composite nanolubricants were measured at temperatures of 30 to 80 °C. Then, the thermal physical properties of Al2O3-SiO2/PAG composite nanolubricants were measured with a variation of nanoparticle composition ratios and volume concentrations. Tribological properties of the composite nanolubricants were evaluated for different loads and speeds. The experimental investigation for the AAC performance was carried out using Al2O3-SiO2/PAG composite nanolubricants (best metal oxide combination) by varying the composition ratios and volume concentrations. Compound optimization technique using the Taguchi and Response Surface Methodology (RSM) methods were selected to optimize the AAC system. Stability evaluation showed Al2O3-SiO2/PAG composite nanolubricants having an excellent stability condition with no sedimentation observed within a month. It was proven by the measurement of the zeta potential up to 61.1 mV and maintenance of the concentration ratio of UV-Vis spectrophotometer of more than 90%. Thermal conductivity and dynamic viscosity of the composite nanolubricants increased with volume concentration and decreased with temperature. The tribological properties observation with optimal conditions of coefficient of friction (COF) and wear rates were found at 0.02% volume concentration. The COF and wear rates were reduced to 4.49% and 12.99%, respectively. The composite nanolubricants at 60:40 composition ratio was observed to be the most effective composition ratio and recommended by the properties evaluation of the nanolubricants. The maximum COP enhancement was achieved up to 28.10% with 0.015% volume concentration and 60:40 composition ratio of Al2O3-SiO2/PAG composite nanolubricants. Consequently, the AAC system parameter namely composition ratio, compressor speed, initial refrigerant charge, and volume concentrations of 60:40, 900 rpm, 155 g and 0.019% respectively were optimized using the compound optimization technique. The optimization results yield optimum cooling capacity, compressor work, COP, and power consumption of 0.94 kW, 19.20 kJ/kg, 9.05 and 0.62 kW, respectively, with highest desirability of 81.60%. Finally, it can be concluded that 0.019% is the optimum volume concentration for Al2O3-SiO2/PAG nanolubricant. Therefore, 0.019% Al2O3-SiO2/PAG with composition ratio of 60:40 was highly recommended for the optimum performance in AAC system.